SURGICAL REPORT OF A NEPHRECTOMY IN A CANINE PATIENT - Duarte, Grazielly Diniz (2022)
Surgical intervention in animal patients affected by different pathologies is indicated so that they will have a better quality of life. Surgical procedures are now possible due to several advances in intervention technologies that are developed and updated for veterinary surgeons. In many cases, promptness in surgical intervention actions is the line of survival that tutors have available to save the lives of their PETs. Nephrectomy, which is the surgical removal of a kidney, may often be indicated as the only way to save the life of an animal patient. Therefore, knowledge about this surgery is very important. In this report, this surgery and those effects resulting from this intervention were addressed. We conclude by establishing the importance that veterinary medical professionals have in maintaining animal welfare and the importance of always being updated and centered on improving their surgical skills. Our results demonstrated that the applied nephrectomy surgery was performed according to expectations.